109k views
4 votes
Solve the trigonometric equation over the interval [0, 2π)


\large{ {cos}^(2) \theta + √(3) sin \theta cos \theta = 1}
Show your work, thanks!​

User Exslim
by
4.9k points

2 Answers

3 votes

Answer:

θ = 0° , 60°

Explanation:


\cos^2\theta + √(3)\sin \theta \cos \theta = 1

  • Substract both the sides from 1.


=> \cos^2\theta + √(3)\sin \theta \cos \theta - 1 = 1 - 1


=> \cos^2\theta + √(3)\sin \theta \cos \theta - 1 = 0

  • Rearrange the terms in L.H.S.


=> (\cos^2 \theta - 1 )+ √(3) \sin \theta \cos \theta = 0

  • Replace the terms in brackets with '-sin²θ' by using the identity (sin²θ + cos²θ = 1).


=> -\sin^2 \theta + √(3) \sin \theta \cos \theta = 0

  • Take 'sinθ' common from the whole expression in L.H.S.


=> \sin \theta(- \sin \theta + √(3)\cos \theta) = 0

Now solve each part separately :-

1)
\sin \theta = 0


=> \theta = \sin^(-1)0 = 0

2)
-\sin \theta + √(3) \cos \theta = 0

  • Divide both the sides by 'cosθ'.


=> (-\sin \theta + √(3)\cos \theta )/(\cos \theta) = (0)/(\cos \theta)


=> (-sin \theta)/(\cos \theta) + (√(3) \cos \theta)/(\cos \theta) = 0


=> -\tan \theta + √(3) = 0

  • Add both the sides with 'tanθ'.


=> -\tan \theta + √(3) + \tan \theta = 0 + \tan \theta


=> \tan \theta = √(3)


=> \theta = \tan^(-1)√(3) = 60

∴ θ = 0° , 60°

User Roryf
by
5.2k points
3 votes

Answer:

Solution given:


\large{ {cos}^(2) \theta + √(3) sin \theta cos \theta = 1}


1-sin^(2) \theta+√(3) sin \theta cos \theta = 1


1-1 +sin^(2)\theta=√(3) sin \theta cos \theta = 1


Sin\theta(sin\theta -√(3)cos\theta)

Either


sin\theta=√(3) cos \theta


√(sin\theta){cos \theta}=√(3)


Tan \theta =√(3)


Tan \theta =Tan 60,Tan(180+60),Tan (360+60)


\theta =60°,240°,420°

in terms of π is


\theta =⅓π,(4)/(3)π,

Or


Sin\theta=1


Sin\theta=Sin0° ,Sin180°

In terms of π is


\theta=0π,π

so


\theta=0π,⅓π,π,(4)/(3)π,

User Alan Dyke
by
5.2k points